Metatranscriptome-based investigation of flavor-producing core microbiota in different fermentation stages of dajiang, a traditional fermented soybean paste of Northeast China. (1st May 2021) - An, Feiyu; Li, Mo; Zhao, Yue; Zhang, Yan; Mu, Delun; Hu, Xinyu; You, Shengbo; Wu, Junrui; Wu, Rina
Highlights: Meta-transcriptome sequencing was applied on soybean paste for the first time. The core microbes involved in soybean paste fermentation were identified. The microbiota was correlated to the flavor-inducing metabolites. Abstract: Dajiang, or naturally fermented soybean paste, has a unique flavor that is influenced by the resident microflora. However, the association between flavor and the core microbiota is unclear. Recent advances in RNA sequencing have identified genes that are actively expressed in complex microbial communities. To this end, we analyzed the time-dependent changes in the microbiota and the metabolite profiles of Dajiang using metatranscriptome sequencing, HS-SPME-GC-MS and amino acid analysis identified 10 volatile compounds that contribute to the development of soybean paste flavor. Further analysis of the correlation between the active microorganisms and the physicochemical characteristics and flavor substances in soybean paste indicated that Lactobacillus and Tetragenococcus were the core genera affecting chromaticity and flavor. These microorganisms produce enzymes that catalyze a series of metabolic pathways that generate flavor substances. Our findings provide new insights into the role of the microbiota in the development of flavor in fermented foods.